The Impact of Inducing Compelled Body Weight Shifts in Improving Dynamic Balance on Non-Hemorrhagic Stroke Patients - Anugrah, Welya Nesvi; Sudaryanto, Wahyu Tri (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Stroke is a brain attack that occurs suddenly where there is partial or complete disruption of brain function as a result of disruption of blood flow due to blockage or rupture of certain blood vessels in the brain, causing brain cells to lack blood, oxygen or nutrients and ultimately can cause These cells die in a relatively short time. In general, strokes are divided into 2, namely hemorrhagic and non-hemorrhagic strokes. Balance disorders due to loss or decreased motor function make stroke patients vulnerable to falls. The aim of this research is to determine the effect of giving Compelled body weight shift on non-hemorrhagic stroke to improve dynamic balance. Subjects and Method: This research was a quasi experiment conducted in Sri Meranti Village, Rumbai, Pekanbaru, Indonesia, from June 2023. 12 non-hemorrhagic stroke patients were selected using purposive sampling. The dependent variable was dynamic balance. The independent variable was compelled body weight shift. Body dynamic balance was measured using Berg balance scale. Body dynamic balance before and after intervention was examined using . Results: There was a significant increase in balance between the control group and the experimental group in non-hemorrhagic stroke sufferers after the compelled body weight shift was carried out (p<0.001). Conclusion: Compelled body weight shift balance training can be used to improve the body dynamic balance in non-hemorrhagic stroke patients.